A Comparison of Field-Based and Lab-Based Experiments to Evaluate User Experience of Personalised Mobile Devices. (11th April 2013) - Sun, Xu; May, Andrew
Abstract : There is a growing debate in the literature regarding the tradeoffs between lab and field evaluation of mobile devices. This paper presents a comparison of field-based and lab-based experiments to evaluate user experience of personalised mobile devices at large sports events. A lab experiment is recommended when the testing focus is on the user interface and application-oriented usability related issues. However, the results suggest that a field experiment is more suitable for investigating a wider range of factors affecting the overall acceptability of the designed mobile service. Such factors include the system function and effects of actual usage contexts aspects. Where open and relaxed communication is important (e.g., where participant groups are naturally reticent to communicate), this is more readily promoted by the use of a field study.